2019
DOI: 10.1371/journal.pone.0218828
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the major Escherichia coli multidrug transporter AcrB reveals transporter plasticity and redundancy in bacterial cells

Abstract: Multidrug Transporters (MDTs) are major contributors to the acquisition and maintenance of Antimicrobial Resistance (AMR), a growing public health threat of broad concern. Despite the large number of MDTs, the overwhelming majority of the studies performed thus far in Gram-negative bacteria emphasize the supremacy of the AcrAB-TolC complex. To unveil the potential role of other MDTs we studied the behavior of a null AcrB Escherichia coli strain when challenged with chloramphenicol, a bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…A recent experimental survey of several hundred gene knockouts in E. coli , using fluorescent probes as antibiotic surrogates showed that dozens of such efflux transporters could be active and thereby contribute to lowering the steady-state uptake 47 . There is also considerable redundancy and plasticity 75 . Thus, as expected from metabolic control analysis, while there is little effect of single-gene knockouts on fluxes 76 , there can be potentially very large effects on the concentrations of intermediary metabolites 77, 78 or, as in our model, the intracellular concentration of an antibiotic of interest,…”
Section: Discussionmentioning
confidence: 99%
“…A recent experimental survey of several hundred gene knockouts in E. coli , using fluorescent probes as antibiotic surrogates showed that dozens of such efflux transporters could be active and thereby contribute to lowering the steady-state uptake 47 . There is also considerable redundancy and plasticity 75 . Thus, as expected from metabolic control analysis, while there is little effect of single-gene knockouts on fluxes 76 , there can be potentially very large effects on the concentrations of intermediary metabolites 77, 78 or, as in our model, the intracellular concentration of an antibiotic of interest,…”
Section: Discussionmentioning
confidence: 99%
“…EV18 and EVC are highly resistant strains developed in our laboratory and have collected a considerable number of mutations that support resistance to NF and chloramphenicol, respectively 23,24 . The results thus far show that regardless of the antibiotic exposure during evolution (NF or chloramphenicol), the resistant strains have a lower pH i , most likely due to the activation of the mar response.…”
Section: Manipulation Of Ph I With Weak Acids the Existence Of A Cormentioning
confidence: 99%
“…EV18 and EVC are highly resistant strains that originated from E. coli BW25113 cells subjected to an in vitro lab evolution process. They carry multiple mutations that accumulated sequentially to confer high-level resistance, two to three orders of magnitude higher than the wild type strains 23,24 . Per previous findings, the wild-type cells maintain their cytoplasmic pH within a range of pH 7.4-7.7 over an external pH range of 6.0-8.1 [13][14][15] .…”
mentioning
confidence: 99%
“…Adaptive evolution studies have begun exploring how certain antibiotic pressures influence the evolution of resistance. For instance, studies using a “morbidostat”—a continuous culture device that dynamically adjusts antibiotic concentrations to inhibitory levels—have found numerous targets that can be readily mutated to promote resistance ( 9 11 ), as well as identifying how drug switching can limit the evolution of resistance ( 12 ). While these studies have provided pivotal insights for this field, the morbidostat design causes antibiotic concentrations to rise to levels that exceed clinically relevant concentrations due to toxicity for patients ( 13 ).…”
Section: Introductionmentioning
confidence: 99%